2015
DOI: 10.3347/kjp.2015.53.5.571
|View full text |Cite
|
Sign up to set email alerts
|

High Malaria Prevalence among Schoolchildren on Kome Island, Tanzania

Abstract: In order to determine the status of malaria among schoolchildren on Kome Island (Lake Victoria), near Mwanza, Tanzania, a total of 244 schoolchildren in 10 primary schools were subjected to a blood survey using the fingerprick method. The subjected schoolchildren were 123 boys and 121 girls who were 6-8 years of age. Only 1 blood smear was prepared for each child. The overall prevalence of malaria was 38.1% (93 positives), and sex difference was not remarkable. However, the positive rate was the highest in Izi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 8 publications
(12 reference statements)
6
18
0
Order By: Relevance
“…This is in line with similar studies reported in Nigeria [24,44,45]. Similarly, this was reported in Democratic Republic of Congo [36], Ghana [40], Tanzania [42] and Mozambique [38]. The observed shift in prevalence of malaria from children < 5 years of age to those ≥ 5 years old, may be related to the malaria control policy, which was focused on children under the age of 5 years and pregnant women.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is in line with similar studies reported in Nigeria [24,44,45]. Similarly, this was reported in Democratic Republic of Congo [36], Ghana [40], Tanzania [42] and Mozambique [38]. The observed shift in prevalence of malaria from children < 5 years of age to those ≥ 5 years old, may be related to the malaria control policy, which was focused on children under the age of 5 years and pregnant women.…”
Section: Discussionsupporting
confidence: 90%
“…In other sub-Saharan countries endemic for malaria, the prevalence rate obtained in this study was similar to that reported in the Democratic Republic of the Congo [36], Equitorial Guinea [37], Mozambique [38] and Papua, New Guinea [39]. The figure was however higher than what was reported in Ghana [40], Gambia [41], Tanzania [42] and Kenya [43].…”
Section: Discussionsupporting
confidence: 87%
“…It is also lower than the household-based malaria prevalence of 18.8% (136/735) reported from the southeastern governorate of Hadhramout [32], where over 99.0% of infections being caused by P. falciparum. However, it is substantially lower than those reported for schoolchildren from several African countries, including Malawi (60.0%), Kenya (42.0%), Uganda (27.6%), Cameroon (22.8-33.8%) and Tanzania (21.6-38.1%; 93/244) [33][34][35][36][37][38][39]. In contrast, it is higher than the rates reported among Kenyan children (4.3%) in a nationwide survey and asymptomatic schoolchildren from northwest Ethiopia (6.8%; 26/385) [40,41].…”
Section: Sociodemographic and Risk Factors Associated With Falciparummentioning
confidence: 67%
“…It is also lower than the household-based malaria prevalence of 18.8% (136/735) reported from the south-eastern governorate of Hadhramout [32], where over 99.0% of infections being caused by P. falciparum. However, it is substantially lower than those reported for schoolchildren from several African countries, including Malawi (60.0%), Kenya (42.0%), Uganda (27.6%), Cameroon (22.8-33.8%) and Tanzania (21.6-38.1%; 93/244) [33][34][35][36][37][38][39]. In contrast, it is higher than the rates reported among Kenyan children (4.3%) in a nationwide survey and asymptomatic schoolchildren from northwest Ethiopia (6.8%;…”
Section: Sociodemographic and Risk Factors Associated With Falciparummentioning
confidence: 67%